Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00296-005-0040-0
|View full text |Cite
|
Sign up to set email alerts
|

Synovial proinflammatory cytokines and their correlation with matrix metalloproteinase-3 expression in Behçet’s disease. Does interleukin-1β play a major role in Behçet’s synovitis?

Abstract: The objective of this study has been the well established fact that proinflammatory cytokines and metalloproteinases play a crucial role in the pathogenesis of chronic arthritis as well as the development of pannus, with the eventual erosive changes. Among the proinflammatory cytokines, interleukin-18 (IL-18) has been shown to contribute to the pathogenesis of chronic synovitis by increasing the secretion of interleukin-1beta (IL-1beta) and the tumor necrosis factor-alpha (TNF-alpha) and also stimulating angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 27 publications
5
27
0
1
Order By: Relevance
“…The increase in IL-1β in the supernatant of P3 airway epithelial supernatants was approximately 30 pg/ml. This level is in 4-fold greater excess than found in synovial fluid from patients with rheumatoid arthritis (38). Finally, to confirm the physiological relevance of our 2D system, we used air-liquid interface culture conditions.…”
Section: Sm In the Small Airways Of Copd Patients Involucrin Is A Comentioning
confidence: 99%
“…The increase in IL-1β in the supernatant of P3 airway epithelial supernatants was approximately 30 pg/ml. This level is in 4-fold greater excess than found in synovial fluid from patients with rheumatoid arthritis (38). Finally, to confirm the physiological relevance of our 2D system, we used air-liquid interface culture conditions.…”
Section: Sm In the Small Airways Of Copd Patients Involucrin Is A Comentioning
confidence: 99%
“…Thus, they speculated that IL1ra and TGF-β might serve as protective factors against cartilage destruction. Pay et al [29] also reported that BD and RA patients had higher synovial IL-1β than OA patients. MMP-3 and proinlammatory cytokines except IL-1β were expressed in small quantities in BD synovitis; this may explain the non-erosive character of BD arthritis.…”
Section: Humoral Protective Factors In Synovial Luid or Bloodmentioning
confidence: 92%
“…It is thought that various proteins (especially the proteins that contain CARD, and pyrin) affect production of IL-1ß mediated caspase-1 activation. 25,26 Many of the diseases characterized by fever, anemia and increased acute phase proteins may be associated with increased IL-1ß production and bioactivity. 27 Additionally, the diseases in this group carry anomalies in a few Nod-like receptor (NLR) signal pathways as shown in cryopyrinopathy.…”
Section: Discussionmentioning
confidence: 99%